Solving degree, last fall degree, and related invariants. (January 2023) - Caminata, Alessio; Gorla, Elisa
Abstract: In this paper we study and relate several invariants connected to the solving degree of a polynomial system. This provides a rigorous framework for estimating the complexity of solving a system of polynomial equations via Gröbner bases methods. Our main results include a connection between the solving degree and the last fall degree and one between the degree of regularity and the Castelnuovo–Mumford regularity.